Macroanatomic studies on the stomach of camel - Hasan Erden; M. Kamil Öcal; Necdet Güzel; Erkut Kara; İlknur Öğüt (Eurasian Journal of Veterinary Sciences)
Work was undertaken to elucidate the macroanatomic details of the stomach of the camel. Fifteen adult healthy one-humped camels (Camelus dromedarius) were used. The abdominal organs were kept in situ and their relations to the stomach were examined. The anatomic structure of the camel stomach was compared in other ruminants, and the functional significance of the differences is discussed. It was observed that the stomach of the camel is composed of four compartments (rumen, reticulum, omasum and abomasum), as in all ruminants. On the contrary, they differ greatly in shape and structure from the typical design encountered in the ruminants. It has a capacity of approximately 80 litres. It extended from the diaphragm to the pelvic inlet and occupied the major portion of the abdominal cavity. The rumen was divided into a relatively small cranioventral and a large caudodorsal sacs. The cra-nioventral sac was composed of so-called 'Water sac' or 'glandular sac' and non glandular area. Intemally the glandular sacs consist of smaller compartments divided by strong longitudinal bands and most of these compartments are again sub-divided by transverse bands, thus giving them a honey comb appearance. The mucous membrane of the rumen was not studded with papillae. The reticulum is a pear shaped organ and unlike other ruminant. The mucous membrane of the reticulum formed deep pouches which are separated from each other by muscular bands. Each pouch was again divided and sub-divided to form many layers. The mucous of the pouches are studded with very small rounded papillae. It was determined that there is a metallic ring one of the camel reticulum. The omasum was a long colon-shaped organs and very different from the omasum of the other domestic ruminants. The mucous membrane was thrown into about 50-60 longitudinal folds which gives a leafy appearance to this organ. Intemally the abomasum was divided into fundic and pyloric parts.